Influence of the type of deformation on the acoustic emission of a magnesium alloy - Papirov, I. I.; Stoev, P. I.; Pikalov, A. I.; Emlyaninova, T. G. (Reports of the National Academy of Sciences of Ukraine, 2016)
The results of a comparative study of the spectra of acoustic emission (AE) of WE43 magnesium alloy with two types of deformation: simple compression and compression with bending, i. e., with the direct contribution of the shear stress components to a deformation are presented. A substantial change in the spectra of AE during a deformation of WE43 magnesium alloy with "switched on" shear stress tensor components is discovered. It is found out that, under the compression with bending, the observed increase in the activity of AE signals and the number of high-amplitude AE pulses is associated with an increase in the contribution of the twinning process due to a shear deformation. It is established that the flexural stress tensor component at the equal-channel angular pressing of blanks of WE43 magnesium alloy significantly contributes to the dispersion of the material structure.